Unmet need for contraception among married adolescent girls and young women in Haramaya Health and demographic surveillance system, Eastern Ethiopia - Hailu, Saba; Assefa, Nega; Dingeta, Tariku; Abdurahman, Chaltu; Adem, Mewardi (Frontiers in Global Women's Health, 2022)
Background The prevalence of unmet need for contraception is the highest in low- and middle-income countries (LMIC). Contraceptive use among young married or unmarried women is lower than that among older women in developing countries. Previous studies generalized the findings to all women of reproductive age and have not investigated psychosocial factors that influence contraceptive use. This study aimed to identify factors associated with unmet need for contraception among young married women in the Haramaya Health and Demographic Surveillance System (HDSS), eastern Ethiopia. Methodology A cross-sectional, community-based study of young married women aged 15–24 years was conducted. A simple random sampling method was used to select 550 young married women. Data were collected using a pretested structured questionnaire. Using adjusted odds ratio (AOR) with a 95% confidence interval (CI), factors associated with unmet need for contraception were identified using multivariable logistic regression analysis. Results The overall prevalence of unmet need for contraception was 154 (30.3%). Adolescents (15–19) (AOR = 2.05, 95% CI: 1.16–3.62), husbands' negative attitude toward contraception (AOR = 2.1, 95% CI: 1.05–4.46), and no previous use of contraception (AOR = 3.9, 95% CI: 2.29–6.71) were significantly and positively associated with unmet need for contraception. On the contrary, young women with secondary education or higher (AOR = 0.55, 95% CI: 0.28–1.084) were negatively and significantly associated with unmet need for contraception. Conclusion The prevalence of unmet need for contraception among young women in Haramaya was high. Unmet need was affected by age, husbands' attitude toward contraceptives, the educational status of women, and previous use of contraception. This study underscored the need to improve girls' educational status to empower them in making contraceptive use decisions with their partners. Programs should also engage male partners who are perceived as key decision-makers when it comes to contraceptive use.